2008
DOI: 10.1210/jc.2008-0855
|View full text |Cite
|
Sign up to set email alerts
|

Impact ofTCF7L2rs7903146 on Insulin Secretion and Action in Young and Elderly Danish Twins

Abstract: The rs7903146 T-allele associates with hepatic insulin resistance and diminished glucose-stimulated plasma insulin secretion. Our study does not provide evidence of a role of TCF7L2 gene expression in sc fat tissue and muscle tissue in the regulation of glucose homeostasis. This suggests that the primary defect of rs7903146 T-allele carriers is impairment of insulin secretion rather than a defect in insulin action in peripheral tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
55
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 34 publications
13
55
1
2
Order By: Relevance
“…Two other recent studies reported a disproportionately increased basal rate of EGP and hepatic insulin resistance in carriers of the risk T allele of rs7903146 [11,35]. Expanding on those recent findings, we found the absolute rate of EGP to be elevated in the basal state as well as during a high physiological insulin infusion in carriers of the risk T allele.…”
Section: Discussionsupporting
confidence: 81%
“…Two other recent studies reported a disproportionately increased basal rate of EGP and hepatic insulin resistance in carriers of the risk T allele of rs7903146 [11,35]. Expanding on those recent findings, we found the absolute rate of EGP to be elevated in the basal state as well as during a high physiological insulin infusion in carriers of the risk T allele.…”
Section: Discussionsupporting
confidence: 81%
“…Human carriers of the TCF7L2 rs7903146 risk T allele have also been reported to have elevated hepatic glucose production [15][16][17][18]. An initial study of alternatively spliced Mature mRNA transcript Transcript number N-terminal C-terminal TCF4 nomination [13] Major pancreatic and liver TCF7L2 isoforms [12 [19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on correlation of TCF7L2 expression levels and risk genotypes have not taken into account the splicing pattern. Furthermore, most of these studies have investigated adipose and/or skeletal muscle tissue [5][6][7][8][9]. While experiments in vitro have shown that a reduction of TCF7L2 expression leads to impaired beta cell function [10,11] we have previously observed increased expression of TCF7L2 in islets of Langerhans from diabetic patients [12].…”
Section: Introductionmentioning
confidence: 99%